Phylogenetic analysis of Komagataeibacter sp.: a cellulose-producer bacteria based on 16S rRNA gene sequences / Nur Aisyah Atikah Alizan and Sarah Shazwani Zakaria - Alizan, Nur Aisyah Atikah; Zakaria, Sarah Shazwani (Universiti Teknologi MARA, Negeri Sembilan, 2021)
Bacteria of the genus Komagataeibacter are described to be the most noteworthy for having several of its species being efficient and strong cellulose producers. The 16S ribosomal RNA (rRNA) gene analysis is often used for the identification and taxonomic classification of these bacteria species. In order to observe the phylogenetic relationship among Komagataeibacter sp., twelve sequences of the 16S rRNA gene with three sequences each for species namely Komagataeibacter europaeus, Komagataeibacter hansenii, Komagataeibacter intermedius and Komagataeibacter xylinus were retrieved from NCBI GenBank database. The sequences were aligned and analysed using PAUP, OrthoANI and BLAST, followed by the phylogenetic tree construction using a Maximum Likelihood method. The parsimony character diagnostic analysis showed very few numbers of parsimonyinformative characters present in the aligned sequences which is only 1.5% of the total characters. The inferred phylogenetic relationships demonstrated the unexpected positioning of K. xylinus (GQ240638: Gluconacetobacter xylinus strain) and K. xylinus (KC11853: G. xylinus strain) into the clades of K. europaeus and K. hansenii respectively. The also very low bootstrap values of the branch points linking the K. europaeus species indicated low support for the produced topologies. The findings of this study indicate that more phylogenies information can be attained by increasing the taxon sampling. In addition, more robust molecular data are needed to infer the phylogenetic relationships between the Komagataeibacter species more accurately.